Paradigma Nusantara for the Advancement of Accounting and Other Social Sciences - Achdiar Redy Setiawan (International Journal of Religious and Cultural Studies, 2022)
This article discusses the invitation to realize the advancement of social science in general that is more contextual in the Nusantara. In the context of accounting, there are several approaches that can be used in research, including positivist, interpretive, critical postmodernist and religious. Generally, in the context of Indonesia (perhaps in other places as well), positivism is still the dominant and most widely used paradigm in the development of social sciences. Contextually, in the author's view, when discussing the advancement of accounting science (and also social science in general) in the Nusantara, the paradigm that must be referred to is the Paradigma Nusantara. The results of research using the Paradigma Nusantara are believed to be more appropriate in its implementation because it is in harmony with the natural thinking, feeling and social and cultural behavior of the local community. At the same time, the development of science aims to raise and present the rich treasures of local wisdom whose values ​​have been internalized, explored and practiced by local people. This article is an initial discourse to look at, measure and filter (re)write noble values ​​which are actually more relevant to be used as guidelines for all activities of daily life.